Inventory Management Practices and Challenges: An Exploratory Study - Abdelrahim Alsoussi; Khaldoun Tahboub (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
Inventory management is crucial for organizational performance, yet a significant gap exists between theoretical models and practical applications. This study explores the inventory management practices and challenges among Jordanian companies across various industries. Given the limited empirical research on this topic in Jordan, a qualitative approach was adopted using semi-structured interviews with representatives from 45 manufacturing, retail, and service companies. The findings reveal a significant gap between theoretical inventory management models and their practical application among participating companies. The common challenges of inventory management were also identified and found to include the lack of formal cost calculation methods, limited technological adoption, supply chain disruptions, and reliance on managerial intuition over data-driven decision-making. The study underscores the need to develop flexible, context-specific inventory models and enhance technological integration, particularly for Small and Medium-Sized Enterprises (SMEs). The study also found that company size significantly affects inventory management, where smaller companies lacked specialized personnel and relied on informal approaches using basic tools like spreadsheets, leading to inefficiencies and limited responsiveness to demand fluctuations. A set of recommendations for practitioners was provided, including adopting adaptable inventory strategies, investing in technology, improving demand forecasting, and strengthening supplier relationships. The study also highlights the importance of bridging the gap between inventory theory and practice, offering valuable insights for academics and practitioners aiming to optimize inventory management in developing economies like Jordan.